Identification of Aesthetic Values ​​& Philosophy of Batik Patterns with Image Processing Techniques (International Journal of Psychosocial Rehabilitation, 2020)
A cultural object has a unique aesthetic value, the value becomes a philosophical identity of a nation, by recognizing a batik pattern means indirectly trying to understand the way of thinking and the life of the maker, the introduction of batik patterns in this study uses an image processing technique by recognizing patterns and the form of a motive, batik data collection is done by dividing the data into two namely training data and testing data, the developed application is made into two parts desktop and mobile applications while the dataset is in the form of images, the results of this study are we can determine and know the value batik motifs by relying on images or images of batik along with its philosophical values.